Morinda citrifolia linn leaf extract possesses antioxidant activities and reduces nociceptive behavior and leukocyte migration - Serafini, Mairim Russo (2011)
This is a copy of an article published in the Journal of Medicinal Food© 2011 - copyright Mary Ann Liebert, Inc.; Journal of Medicinal Food is available online at: http://online.liebertpub.com